(untitled) (American Journal of Islam and Society, 2012)
Although the revolution in Syria is unfolding within the country’s modern political borders, what is going on can only be understood by placing it in a larger historical context, which includes the adjacent geographical areas of Bilad al-Sham. Without such a broader view, the complexity of Syria’s current reality can neither be appreciated, nor can its consequences be accounted for and its future anticipated. Probably in no country is the mess of a land’s colonial legacy more visible than it is in Syria. This legacy’s pathway marks the country’s future development, and its implications are facing the revolution today with arduous challenges. The resulting complexity extends beyond the political dimension, for a similar level of complexity exists at the meta-cultural level as well. Furthermore, the change in Syria has regional consequences: It will institutionalize the Arab revolution as an unavoidable political force and energize the process of cultural reformation and the recovery of a civilizational Muslim identity. This essay first examines the region’s historical background and the consequences of the Ottoman order’s disintegration. Second, it analyzes the national identity dilemmas faced by the Arab world after colonialism, how non-Muslims reacted to them, and the two political paths that those countries pursued. Third, the essay discusses the formation of grievances among Syrian minorities in particular. Fourth, the politics of the post-independence era are presented, highlighting the promise of the development upon which Syria was embarking. The essay then investigates the politics and social conditions that led to a dictatorship of three overlapping types: ideological left, sectarian, and neoliberal. Before focusing on the ongoing revolution, a note on Islamic activism is presented due to the fact that Islamic meanings have always been the impetus propelling the people’s resistance. The revolutionary realities on the ground are then elaborated upon, emphasizing how the regime’s extreme violence against peaceful protest intersects with historical social alignments. Lastly, the essay discusses the geopolitical context in which the Syrian revolution is taking place, which at once makes it hard to prevail and makes any of its outcomes highly consequential for the whole region.